Budidaya Maggot (Hermetia illuens) dengan menggunakan beberapa media - Mudeng, Nico E.G.; Mokolensang, Jeffrie F.; Kalesaran, Ockstan J.; Pangkey, Henneke; Lantu, Sartje (Universitas Sam Ratulangi, 2018)
The purpose of this study was to determine the best culture medium for producing maggot (Hermetia illucens) and to determine the production quantity in each different medium. Â This research was controlled two times a day at 09:00 a.m. and 16:00 p.m. Cultivation media were prepared from coconut pulp, tofu pulp, rice bran and restaurant wastes. Each medium was weighed as much as one kg and then placed into a culture container. The research used Completely Randomized Design consisting of 4 treatments, each with three replications. The parameters observed consisted of temperature and pH of the media Â measured at 07.00 am and 17.00 pm, and maggot production measured on the last day. During the ten days of experiment, the production of maggot in the treatment using restaurant waste media was significantly different as compared to other treatments. This study found that a good medium for the production of maggot was prepared using restaurant waste.Â Keywords: Hermetia illucens, coconut pulp, restaurant waste